Computational Investigation of Fluidized Drying of Paddy by Air with a State Variable of Time - Shakidi, Siti Suaidah (IRC, 2017)
In study of improvement drying paddy, experimental and industrial investigation for paddy are inefficient in both time and resources compare to computational investigation. Experimental and industrial investigation are limited to estimate and predict the output parameter compared to numerical and computational investigation. A mathematical model of fluidized drying of paddy by air with a state variable of time were formulate. Drying process were simulate computationally for various given boundary conditions. Literature review were studied to understand the drying formula used for drying paddy and a quality paddy specification. Mathematical formulation for numerous heat and mass transfer equations for drying paddy were modified from previous study. Initial condition used based on previous study was initial moisture content of paddy of 24% dry basis, air temperature of 115oC, air velocity of 2.3 ms-1. For the fluidized dryer specification, this project also used the same parameter as the experimental fluidized industrial dryer with these criteria; bed thickness 10cm, and 4.85 x 0.97 m2 bed area. With the same initial condition used from the experimental study, computational investigation were done using numerical model and 4th order Runge-Kutta formulation. Coding in MATLAB was applied to numerical calculation of partial differential model and results were simulated for both data reported from experimental and mathematical model. The two result were compared and showed that the computational approach were capable to predict moisture content of paddy. Graph plotted by simulation shows very insignificant difference from result obtained by experimental results. This computational approach provide easy and comprehensive method for research and development of fluidized drying in further improvement.